2018
DOI: 10.1017/s1355617718000073
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Patients With Neuropsychiatric and Non-neuropsychiatric Systemic Lupus Erythematosus: A Systematic Review and Meta-analysis

Abstract: The data obtained indicate greater cognitive impairment among NP-SLE patients than among nonNP-SLE patients, at least for the cognitive domains of visuomotor coordination, attention, executive function, visual learning and memory, and phonetic fluency. The identification and definition of cognitive deficits in SLE patients is necessary to develop adequate cognitive remediation programs to improve functional outcomes. (JINS, 2018, 24, 629-639).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
(62 reference statements)
2
13
0
2
Order By: Relevance
“…Cognitive dysfunction (CD) is one of the most common clinical manifestations of NPSLE. 1 Previous research studies 2,3 suggest that CD can occur in SLE before it develops into NPSLE, and can manifest as a mild cognitive impairment to severe dementia which affects the patients’ quality of life. Due to the absence of uniform screening methods, the reported prevalence varies from 20% to 80%.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive dysfunction (CD) is one of the most common clinical manifestations of NPSLE. 1 Previous research studies 2,3 suggest that CD can occur in SLE before it develops into NPSLE, and can manifest as a mild cognitive impairment to severe dementia which affects the patients’ quality of life. Due to the absence of uniform screening methods, the reported prevalence varies from 20% to 80%.…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms of neuropsychiatric SLE may vary, such as mild mood disorder to psychosis or status epilepticus that accounts for up to 19% of deaths in patients with SLE [46]. Moreover, neuropsychological studies have found that SLE patients with nonneuropsychiatric systemic lupus erythematosus (non-NPSLE) can be affected with cognitive abnormalities [7]. The review of 22 published studies found that cognitive impairment was seen in 72% to 75% of non-NPSLE patients, which may be associated with lower health-related quality of life indices [8].…”
Section: Introductionmentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is an autoimmune disease characterized by high levels of autoantibody and damages in multiple organs, including central nervous system [1, 2]. Neuropsychiatric lupus erythematosus (NPSLE) has been reported as a common syndrome of SLE [3, 4]. It is widely accepted that tissue damage in SLE is associated with autoantibody production and immune complex formation and deposition [5].…”
Section: Introductionmentioning
confidence: 99%